A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

Oxidative potential of particulate matter and its association to respiratory health endpoints in high-altitude cities in Bolivia - Lucille Borlaza-Lacoste; Valeria Mardoñez; Anouk Marsal; Ian Hough; Vy Ngoc Thuy Dinh; Pamela Dominutti; Jean-Luc Jaffrezo; Andrés Alastuey; Jean-Luc Besombes; Griša Močnik; Isabel Moreno; Fernando Velarde; et al. (Environmental Research, 2024)

Trade-off between growth and reproduction in Argopecten purpuratus (L.) scallops exposed to medium-term hypoxia and acidification - Rosa Cueto-Vega; Jonathan Flye-Sainte-Marie; José Luis García-Corona; Fernando Palacios; Fred Jean; Arturo Aguirre-Velarde; Patricia Gil-Kodaka; Jaime Mendo; Gérard Thouzeau (Aquaculture, 2024)

Environmental gradualism explains variation in pollination systems of columnar cacti: Phylogenetic and trait evolution analyses - Damian Freilij; Daniel Larrea‐Alcazar; Ramiro Pablo Lopez; Fernando Velarde Simonini; Kazuya Naoki; Cecilia Bessega (Global Ecology and Biogeography, 2023)
Aim The geographical dichotomy hypothesis (GDH) states several flowering plant groups have specialized pollination systems in tropical areas where resources are more reliable and pollinator communities tend to be more stable, than in extratropical areas. Our main goal was to understand the scope of the GDH and/or gradual environmental variation considering the evolutionary history of the pollination traits. Location Neotropical tropics and adjacent extratropics. Major taxa studied Columnar cacti. Methods Using a database composed of ~54 columnar cacti species (31.7% of the global columnar cactus species), four complex traits were analysed: pollination syndromes, reproductive systems, type of anthesis, and duration of anthesis. We conducted generalized linear models (GLMs), phylogenetic regressions, evolutionary trait optimization, and multivariate models with 19 bioclimatic variables and potential evapotranspiration. Results Weak phylogenetic signal was detected for all traits, giving consistent results between GLMs and phylogenetic regression analysis. The pollination syndrome and duration of anthesis varied with latitude, in contrast to the reproductive system and the type of anthesis. In the Southern Hemisphere, the pollinators were more diverse and the duration of anthesis was longer. Different evolutionary paths between hemispheres were detected and optimization showed a complex pattern in the evolution of traits, suggesting high homoplasy with multiple transformations by convergence and/or parallelism. The environmental models showed thermic seasonality may be at the core of the latitudinal variation of the pollination system. Main conclusions We did not detect a geographical dichotomy in pollination systems of the cacti, but rather a gradual change in different pollination attributes. Therefore, instead of a GDH, we propose an environmental gradient hypothesis (EGH). Environmental variables may be explaining the variation detected in pollination system traits by conditioning floral properties (morphology, phenology), diversity and distribution of pollinators, and/or coevolution occurrence. The complexity implied in these traits is consistent with high homoplasy levels and a differential evolutionary history between the hemispheres.

Nitrogen use efficiency and soil chemical composition in small-scale dairy systems - Dixan Pozo-Leyva; Felipe López-González; Fernando Casanova-Lugo; Sirley Carrillo-Hernández; José Velarde-Guillen; Carlos Manuel Arriaga-Jordán (Tropical Animal Health and Production, 2021)

Coral Reef Degradation Differentially Alters Feeding Ecology of Co-occurring Congeneric Spiny Lobsters - Patricia Briones-Fourzán; Lorenzo Álvarez-Filip; Cecilia Barradas-Ortíz; Piedad S. Morillo-Velarde; Fernando Negrete-Soto; Iris Segura-García; Alberto Sánchez-González; Enrique Lozano-Álvarez (Frontiers in Marine Science, 2019)

Identifying, attributing, and overcoming common data quality issues of manned station observations - Stefan Hunziker; Stefanie Gubler; Juan Calle; Isabel Moreno; Marcos Andrade; Fernando Velarde; Laura Ticona; Gualberto Carrasco; Yaruska Castellón; Clara Oria; Mischa Croci‐Maspoli; Thomas Konzelmann; et al. (International Journal of Climatology, 2017)
In situ climatological observations are essential for studies related to climate trends and extreme events. However, in many regions of the globe, observational records are affected by a large number of data quality issues. Assessing and controlling the quality of such datasets is an important, often overlooked aspect of climate research. Besides analysing the measurement data, metadata are important for a comprehensive data quality assessment. However, metadata are often missing, but may partly be reconstructed by suitable actions such as station inspections. This study identifies and attributes the most important common data quality issues in Bolivian and Peruvian temperature and precipitation datasets. The same or similar errors are found in many other predominantly manned station networks worldwide. A large fraction of these issues can be traced back to measurement errors by the observers. Therefore, the most effective way to prevent errors is to strengthen the training of observers and to establish a near real‐time quality control ( QC ) procedure. Many common data quality issues are hardly detected by usual QC approaches. Data visualization, however, is an effective tool to identify and attribute those issues, and therefore enables data users to potentially correct errors and to decide which purposes are not affected by specific problems. The resulting increase in usable station records is particularly important in areas where station networks are sparse. In such networks, adequate selection and treatment of time series based on a comprehensive QC procedure may contribute to improving data homogeneity more than statistical data homogenization methods.

Identification of a gammaherpesvirus belonging to the malignant catarrhal fever group of viruses in Pyrenean chamois (Rupicapra p. pyrenaica) - Xavier Fernández-Aguilar; Fernando Esperón; Oscar Cabezón; Roser Velarde; Gregorio Mentaberre; Verónica Delicado; María Jesús Muñoz; Emmanuel Serrano; Santiago Lavín; Jorge Ramón López-Olvera (Archives of Virology, 2016)